Sosialisasi Manajemen Risiko Judi Online pada Remaja di SMAN 9 Cirebon - Diddo Adding Adove; Firda Mokodongan; Sujeni Sujeni; Gilang Pranajasakti; Grara Vema Tuzauna (Institut Nalanda, 2024)
The online gambling prevention socialization program at SMAN 9 Cirebon is a strategic step in increasing students' understanding of the risks posed by this activity. This activity is designed through various educational methods, such as seminars, compiling information materials in the form of videos and brochures, and interactive discussions involving students, teachers, and parents. This program also focuses on improving students' skills in decision-making, stress management, and effective communication to build collective awareness in preventing online gambling. The main challenges in implementing this program include limited time and resources to reach all students as a whole, as well as the difficulty of changing internet usage habits without supervision. In addition, the readiness of teaching staff in dealing with educational technology and limited school infrastructure are also obstacles that need to be overcome. Therefore, the implementation of character education that instills discipline, respect for teachers, and moral values ​​consistently becomes an important part of the prevention strategy. This program is expected to create a safer and healthier learning environment, where students have a better understanding of the risks of online gambling and are able to avoid its negative influences. The output targets to be achieved include increasing students' understanding of the dangers of online gambling, forming collective awareness in the school environment, and having more effective policies and strategies in preventing online gambling.